The Effectiveness of Principal’s Academic Supervision in Enhancing Teachers’ Pedagogical Competency: A Systematic Literature Review - Siahaan, Sarifah (PPSDP International Journal of Education, 2025)
This study aims to examine the role and effectiveness of principal’s supervision in improving teachers’ performance and pedagogical competence through a Systematic Literature Review (SLR) approach. By analyzing relevant literature on academic supervision in Indonesian primary and secondary education, the study finds that effective, structured, and continuous supervision enhances teacher skills in lesson planning, subject mastery, and the use of appropriate teaching methods. Principal supervision not only strengthens professional competence but also fosters motivation and a conducive learning environment. The study highlights that the success of supervision is influenced by the principal’s leadership, school culture, and teacher involvement. Additionally, it identifies key challenges such as limited time and resources that hinder effective supervision. Overall, the findings emphasize the need for a collaborative, feedback-based supervision model and suggest that strengthening principals’ capacity as academic supervisors is essential to improving teaching quality and informing educational policies that support teacher development and school improvement.